-2(5x=1)=6(33-10x)

Simple and best practice solution for -2(5x=1)=6(33-10x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5x=1)=6(33-10x) equation:



-2(5x=1)=6(33-10x)
We move all terms to the left:
-2(5x-(1))=0
We multiply parentheses
-10x+2=0
We move all terms containing x to the left, all other terms to the right
-10x=-2
x=-2/-10
x=1/5

See similar equations:

| (5x/2x+7)=3 | | 8x+14=170 | | 7k+2k=18 | | -u/7=-52 | | -16j=-17j-13 | | -8+3x=14 | | v/5-10=-7 | | -21=-y/8 | | -7v-8v=-14+1-3v+1 | | 10+x3=4 | | -12+13h=20+11h | | -6y+6=-2y- | | X-3=7+5x+4-2 | | n/18=108 | | 21=3x+3(-x+7) | | 3(x-4)²-2=25 | | 18/n=109.8 | | -1/4x=-9/4x+1/8 | | 3(x-4)²2=25 | | d-19=-18d | | 8u+8=9 | | X-3=7+5x4-2 | | c-9/5=5 | | -15-4x=-x+6 | | 7x-1x-9=2(4x+9) | | 9+p8=7 | | 6^7x=390 | | -7x-6x=-4+x-3-7 | | -2-9b=-14-7b | | 6u−4u=8 | | 37.2=x | | 2(-3x-4)=-3x+3 |

Equations solver categories